2017
DOI: 10.1111/ina.12425
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying fine particle emission events from time‐resolved measurements: Method description and application to 18 California low‐income apartments

Abstract: PM 2.5 exposure is associated with significant health risk. Exposures in homes derive from both outdoor and indoor sources, with emissions occurring primarily in discrete events. Data on emission event magnitudes and schedules are needed to support simulation-based studies of exposures and mitigations. This study applied an identification and characterization algorithm to quantify time-resolved PM 2.5 emission events from data collected during 224 days of monitoring in 18 California apartments with low-income … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 59 publications
3
33
0
Order By: Relevance
“…Our values of G and gfalse(Tfalse)¯ can also be compared with those derived from in situ measurements of multiple household activities that include cooking to give a broader understanding of their significance. Chan et al calculated emission rates for 836 cooking and non‐cooking events in 18 dwellings in California, finding a mean source strength and emission rate of 30 mg and 1.72 mg/min, respectively, which are broadly similar to ours. Dacunto et al identified source strengths and emission rates of 1.4 mg and 0.1 mg/min for oven cooked frozen pizza, 72.5 mg and 9.5 mg/min for toasting of bread (90%‐95% charred), 18.3 mg and 1.6 mg/min for fried salmon, 24.3 mg and 2.1 mg/min for fried pork chop, 19.9 mg and 3.8 mg/min for cigarette smoking, 16.9 mg and 1.3 mg/min for the burning of stick incense, and 215.4 mg and 16.4 mg/min for an open fire.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Our values of G and gfalse(Tfalse)¯ can also be compared with those derived from in situ measurements of multiple household activities that include cooking to give a broader understanding of their significance. Chan et al calculated emission rates for 836 cooking and non‐cooking events in 18 dwellings in California, finding a mean source strength and emission rate of 30 mg and 1.72 mg/min, respectively, which are broadly similar to ours. Dacunto et al identified source strengths and emission rates of 1.4 mg and 0.1 mg/min for oven cooked frozen pizza, 72.5 mg and 9.5 mg/min for toasting of bread (90%‐95% charred), 18.3 mg and 1.6 mg/min for fried salmon, 24.3 mg and 2.1 mg/min for fried pork chop, 19.9 mg and 3.8 mg/min for cigarette smoking, 16.9 mg and 1.3 mg/min for the burning of stick incense, and 215.4 mg and 16.4 mg/min for an open fire.…”
Section: Resultssupporting
confidence: 82%
“…Our values of G and g(T) can also be compared with those derived from in situ measurements of multiple household activities that include cooking to give a broader understanding of their significance. Chan et al 11 Table 3 shows that the particle counts exceeded 2 × 10 6 particles/L in 10 of the 24 tests. Here, the Grimm may experience coincidence errors where multiple particle may be seen as one larger particle.…”
Section: Emission Ratesmentioning
confidence: 93%
See 2 more Smart Citations
“…The work followed a similar procedure as that described in ISO 16890 and in Section 2 herein, albeit with the following exceptions: (1) 194 long-term average trimodal ambient aerosol distributions from around the world were used, rather than a single static urban or rural bimodal distribution; (2) fractional filter removal efficiency data from laboratory tests that measured down to as small as 30 nm were used (and the remaining data were fit with a model down to just a few nanometers) [35]; and (3) in addition to estimating PM2.5 and UFP removal efficiencies assuming 100% outdoor air delivery, PM2.5 and UFP removal efficiencies for indoor particles of outdoor origin were also estimated assuming ambient aerosols penetrated through the building envelope of a typical residential building with a recirculating HVAC system. This approach allowed for estimates of the PM2.5 and UFP removal efficiency for various filters for indoor particles of outdoor origin, which is a condition that frequently occurs in many buildings when indoor sources are not present [36][37][38][39][40]. The number and volume distributions from the 194 outdoor particle size distributions reviewed in Azimi et al (2014) [29] are shown in Figure 2, with the number and volume distributions from Jaenicke (1993) [31] overlaid.…”
Section: How Relevant Are the Historical Ambient Aerosol Distributionmentioning
confidence: 99%